Glycemic index and insulin index after a standard carbohydrate meal consumed with live kombucha: A randomised, placebo-controlled, crossover trial - Atkinson, Fiona S.; Cohen, Marc; Lau, Karen; Brand-Miller, Jennie C. (Frontiers in Nutrition, 2023)
Kombucha is a complex probiotic beverage made from fermented tea, yet despite extensive historical, anecdotal, and in-vivo evidence for its health benefits, no controlled trials have been published its effect on humans. We conducted a randomised placebo-controlled, cross-over study that examined the Glycemic Index (GI) and Insulin Index (II) responses after a standardised high-GI meal consumed with three different test beverages (soda water, diet lemonade soft drink and an unpasteurised kombucha) in 11 healthy adults. The study was prospectively registered with the Australian New Zealand Clinical Trials Registry (anzctr.org.au: 12620000460909). Soda water was used as the control beverage. GI or II values were calculated by expressing the 2-h blood glucose or insulin response as a percentage of the response produced by 50 g of glucose dissolved in water. There was no statistically significant difference in GI or II between the standard meal consumed with soda water (GI: 86 and II: 85) or diet soft drink (GI: 84 and II: 81, (p = 0.929 for GI and p = 0.374 for II). In contrast, when kombucha was consumed there was a clinically significant reduction in GI and II (GI: 68, p = 0.041 and II: 70, p = 0.041) compared to the meal consumed with soda water. These results suggest live kombucha can produce reductions in acute postprandial hyperglycemia. Further studies examining the mechanisms and potential therapeutic benefits of kombucha are warranted.